2017
DOI: 10.1002/jmv.24768
|View full text |Cite
|
Sign up to set email alerts
|

RSV associated hospitalizations in children in Karachi, Pakistan: Implications for vaccine prevention strategies

Abstract: Major progress is being made in vaccines against Respiratory Syncytial Virus (RSV), with multiple vaccine candidates currently in the clinical phase of development. Making an investment case for public sector financing of RSV vaccine will require estimation of burden, cost-effectiveness and impact. The aim of this study is to determine the proportion, age distribution and clinical spectrum of RSV associated hospitalizations in children in Karachi, Pakistan. A three years prospective study was conducted at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
(17 reference statements)
2
13
1
Order By: Relevance
“…Karachi is the capital of Sindh province in Pakistan, and is one of the most populous cities in the world with a population of approximately 20 million. The detail setting and other methods are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Karachi is the capital of Sindh province in Pakistan, and is one of the most populous cities in the world with a population of approximately 20 million. The detail setting and other methods are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Jan 2008-Dec 2008 51 16 y 51 25.0 51 Early spring to winter, with a peak from Jan to Apr 51 Hong Kong Jan 2004-Dec 2004 52 3 y 52 11.6 52 No winter seasonality 3 57 All ages 57 8.9 57 Detected most month of the year with a peak from Jun to Oct 57 Aug 2009-Jun 2012 63 < 5 y 63 19 63 Peak in Sep coinciding with the rainy season 63 Abbreviations: NA, not available; RSV, respiratory syncytial virus.…”
Section: Rsv-associated Disease Burdenmentioning
confidence: 99%
“…The most noteworthy rate of RSV identification was in infants under 3 months of age (48/168, 29%), which represented 22% of all RSV distinguished. Most normal determination in RSV positive babies (<12 months of age) was bronchiolitis trailed by pneumonia whereas in other study, 7% (84 out of 1150) of the cases were identified with the presence of HMPV, 67% (56 out of 84) of which were children under 1 year of age, and these cases were characterized by bronchiolitis trailed by pneumonia …”
Section: Discussionmentioning
confidence: 63%
“…RSV appeared to be more incident from August to October and highest in September. Susceptibility increased in rainy seasons . HMPV was detected in 7% of the cases in the above scenario, most of which were children under 1 year of age …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation